Ukrainian rhotic consonants in comparison to Russian: An acoustic study - Dmytro Hrytsu (Estudios de Fonética Experimental)
This short paper maintains a discussion on the nature of rhotic consonants in two different but genetically related languages (Ukrainian and Russian). The main goal of the paper is carrying out a modern acoustic study about rhotic realizations in the two target languages, as well as putting forward some considerations about a possible sound change. Acoustic analysis is carried out using LPC and FFT measurements in order to capture the difference in rhotic realizations. The results allow for a description of the acoustic properties of the Ukrainian language, and suggest the existence of an ongoing simplification process of rhotic consonants in both languages.